2019
DOI: 10.1097/sla.0000000000002825
|View full text |Cite
|
Sign up to set email alerts
|

Data-driven Development of ROTEM and TEG Algorithms for the Management of Trauma Hemorrhage

Abstract: We describe a systematic approach to define threshold parameters for ROTEM and TEG. These parameters were incorporated into algorithms to support data-driven adjustments of resuscitation with therapeutics, to optimize damage control resuscitation practice in trauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
119
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 112 publications
(126 citation statements)
references
References 32 publications
1
119
0
2
Order By: Relevance
“…The same cut-off values have been recommended by the consensus group on viscoelastic test-based transfusion guidelines for early trauma resuscitation and the German AWMF guidelines on the management of multiple traumas [164][165][166]. Similar cut-off values are used in the European multicenter RCT iTACTIC (implementing Treatment Algorithms for the Correction of Trauma-Induced Coagulopathy; ClinicalTrials.gov, ID: NCT02593877): A5 FIB < 10 mm for fibrinogen substitution and (A5 EX -A5 FIB ) < 30 mm for platelet transfusion [167]. This is also in line with the FIBTEM cut-off values published by Na et al [29] to predict massive bleeding in total hip replacement arthroplasty.…”
Section: In Trauma and Orthopedic Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…The same cut-off values have been recommended by the consensus group on viscoelastic test-based transfusion guidelines for early trauma resuscitation and the German AWMF guidelines on the management of multiple traumas [164][165][166]. Similar cut-off values are used in the European multicenter RCT iTACTIC (implementing Treatment Algorithms for the Correction of Trauma-Induced Coagulopathy; ClinicalTrials.gov, ID: NCT02593877): A5 FIB < 10 mm for fibrinogen substitution and (A5 EX -A5 FIB ) < 30 mm for platelet transfusion [167]. This is also in line with the FIBTEM cut-off values published by Na et al [29] to predict massive bleeding in total hip replacement arthroplasty.…”
Section: In Trauma and Orthopedic Surgerymentioning
confidence: 99%
“…Impaired thrombin generation with the need for plasma transfusion or four-factor PCC administration is considered in our trauma algorithm if CT EX > 80 s and A5 FIB ≥ 9 mm according to the consensus group on viscoelastic test-based transfusion guidelines for early trauma resuscitation and the German AWMF guidelines on the management of multiple trauma [164][165][166]. This is also in line with the iTACTIC protocol [167]. In severe traumatic hemorrhage, fixed-ratio RBC and plasma transfusion is not effective to treat ATC and to reduce mortality [12][13][14][15][16][17]171].…”
Section: In Trauma and Orthopedic Surgerymentioning
confidence: 99%
“…infections, volume overload, immunosuppression and kidney injury) [11][12][13][14] and it has been shown that a reduced transfusion requirement improved clinical outcomes including mortality [15,16]. Therefore, a factor-based, goal-directed coagulation management guided by viscoelastic point of care tests [2] has been proposed as a new approach of haemostatic resuscitation [1,7,[17][18][19]. This coagulation management was proven to decrease transfusion requirement with beneficial outcomes in trauma patients [1,7,17,18].…”
Section: Discussionmentioning
confidence: 99%
“…These assays provide real-time quantification of different aspects of coagulation and yield meaningful results within five minutes of initiating the test. More recently, there has been growing interest in whether these assays can be used to direct blood product transfusion and TXA administration based on alterations in clot initiation, clot strength and clot breakdown (Baksaas-Aasen et al, 2018). Although this approach has been adopted in some centres, high quality evidence from randomized trials is still awaited this knowledge gap will be addressed by the multicentre iTACTIC (implementation of Treatment Algorithms for the Management of Trauma Induced Coagulopathy) trial which has completed recruitment and will report in the next year (Baksaas-Aasen et al, 2017).…”
Section: Goal-directed Resuscitationmentioning
confidence: 99%